2011
DOI: 10.2215/cjn.06270710
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Methicillin-resistant Staphylococcus aureus Is Associated with Higher All-Cause Mortality in Hemodialysis Patients

Abstract: SummaryBackground and objectives Methicillin-resistant Staphylococcus aureus (MRSA) nasal carriage is a recognized risk factor for subsequent endogenous infections. However, the association between MRSA carriage and patient survival in hemodialysis patients has not been established. Design, setting, participants, & measurementsIn March 2007, this prospective cohort study enrolled 306 outpatients under maintenance hemodialysis from a hospital-based dialysis center in Taiwan. They received two consecutive weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 29 publications
2
33
1
1
Order By: Relevance
“…28,30,33,42,43,46 Two of these studies reported the MRSA infection rate during hospitalization of inpatient individuals, 33,43 whereas four studies included data after a long-term follow-up period of outpatient individuals. 28,30,42,46 Because we were interested in the long-term risk of acquiring a MRSA infection, only the data from the latter four studies were used and the data from each study are summarized in Table 3. The estimated risk of MRSA infection was 3.1% (95% CI, 1.9% to 4.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,30,33,42,43,46 Two of these studies reported the MRSA infection rate during hospitalization of inpatient individuals, 33,43 whereas four studies included data after a long-term follow-up period of outpatient individuals. 28,30,42,46 Because we were interested in the long-term risk of acquiring a MRSA infection, only the data from the latter four studies were used and the data from each study are summarized in Table 3. The estimated risk of MRSA infection was 3.1% (95% CI, 1.9% to 4.7%).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is current because it is based on four different studies published after 2011. 28,30,42,46 The high long-term risk of MRSA infection among colonized patients has also been demonstrated among hospitalized patients (another high-risk population), in which Datta et al showed that 23% of hospitalized patients who were MRSA carriers developed a MRSA infection during the following year. 59 It is encouraging that even with this stable trend in colonization after 2000 and the fact that MRSA colonization is closely associated with infection, 60 the rate of MRSA infections among dialysis patients in the United States over the last 8 years has been declining.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is one of the most common causes of hospitalization, morbidity, and mortality among patients with End-Stage Renal Disease (ESRD) who are undergoing hemodialysis (HD), Peritoneal Dialysis (PD), Continuous Ambulatory Peritoneal Dialysis (CAPD), or kidney transplantations [1][2][3]. Endogenous gram-positive cocci, especially Staphylococcus aureus (S. aureus), are the most frequently associated microorganism in long-term dialysis patients, and anterior nares are the most common endogenous SA carrier sites [4].…”
Section: Introductionmentioning
confidence: 99%
“…MRSA colonization in a high-prevalence country was found to be 2-4% in HD patients and 4-6% in dialysis unit personnel. Patients that require HD and are MRSA carriers have a 2.5-fold increase in all-cause mortality [30] . Decolonization techniques including nasal mupirocin and whole body chlorhexidine wash may achieve elimination of Staphylococcus and a risk reduction for major infections in the short term, but development of resistance has been documented.…”
mentioning
confidence: 99%